Innovation and Access to Credit in Export-Oriented Indonesian MSMEs: The Mediating Roles of Competitive Advantage and Strategic Orientation - Agustina Agustina; Wisnu Yuwono; Erilia Kesumahati (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study examines the influence of innovation on access to credit among export-oriented micro, small, and medium enterprises (MSMEs) in Indonesia, with competitive advantage and strategic orientation modeled as mediating variables. It investigates how innovation may strengthen MSMEs’ credibility and competitiveness, thereby improving financial access in global markets.Method: The study adopts a quantitative design and applies Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 440 MSME owners and managers located in Batam, Jakarta, and other areas of Java.Result: The findings indicate that innovation significantly strengthens both competitive advantage and strategic orientation. In turn, competitive advantage and strategic orientation each exert a positive effect on access to credit. The mediation results suggest that innovation indirectly enhances credit access through these strategic and competitive pathways, underscoring the central role of intermediary capabilities in translating innovation into improved financial accessibility.Practical Implications for Economic Growth and Development: The results suggest that promoting innovation-driven strategies among MSMEs can enhance financial inclusion while strengthening competitiveness in export markets. Policymakers and financial institutions may use these insights to refine credit appraisal frameworks and design development programs that recognize and support innovation-led growth, thereby contributing to Indonesia’s economic resilience and export performance.Originality/Value: This study contributes by clarifying the mechanism through which innovation improves access to credit. Whereas prior research has largely emphasized the direct effects of innovation on financial performance or financing access, this study extends the literature by incorporating strategic orientation and competitive advantage as mediators that explain how innovation strengthens MSMEs’ credit opportunities.